PANDANGAN FILSAFAT HUMANISTIK DALAM NOVEL TOTTO-CHAN RELEVANSINYA BAGI PENDIDIKAN DI INDONESIA - Habib, Muhammad Mustofa (Al Tadib : Jurnal Ilmu Pendidikan, 2021)
This article aimed to explore and emerge humanistic philosophy views contained in Totto-chan's novel: The Litle Girl at the Window by Tetsuko Kuroyanagi. The method used in this study was literature study method which was conducted by examining the messages contained in Totto-chan's novel: The Litle Girl at the Window by Tetsuko Kuroyanagi, and other supporting sources. The results of this study indicated that there were some humanistic philosophies contained in the novel including: strengthening the students' confidence in giving meaning to life, opening the way to develop self-ability based on students' freedom and responsibility, guiding the students to find their life using self-motivation and desire to become better, developing original perspective and expression in accordance with the students.